Cleaner Transport Fuels for Cleaner Air in Central Asia and the Caucasus - World Bank (Washington, DC, 2014)
Combating pollution needs to be based on standards supported by enforced regulatory, and physical infrastructure, not always in place in countries in transition from central planning to a market economy. Policymakers in the Central Asia and the Caucus region, however, are recognizing the need for such steps against pollution, demonstrated by their commitment to phase out lead from gasoline. To support these efforts, the Bank undertook a regional study on cleaner transport fuels for urban quality improvement in the region, recognizing that fuel quality improvements should be linked to broader air quality management, to ensure cost-effectiveness, and in addressing these issues, it is therefore possible to build on economies of scale, avoid duplications, allow the transfer of experience, and facilitate intra-regional trade in petroleum products. This lead to this study's observations, and recommendations. The establishment of continuous monitoring of the "classical" pollutants, should permit comparison with international standards, by monitoring fine particles, airborne lead, and ground-level ozone. In turn, facilities with diagnostic equipment, and qualified technicians should be available, including vehicle registration systems. It is recommended that gasoline lead should be eliminated by 2005, sulfur in gasoline should be limited by 2015, benzene reductions should be phased out, and instead introduce the acceptable diesel sulfur specifications, and standards as in developed countries. Considerations should include the installation of isomer units; reevaluation on the role of refineries in gasoline production; and, fuel-quality specifications in privatization biding documents, should ensure predictability of regulations.